Prevalensi Computer Vision Syndrome pada Pemain Valorant di Komunitas Valorant Indonesia Tahun 2024 - Kalayukin, Jenifer; Lesmana, Michael Indra; Goenawan, Kristian (Universitas Kristen Krida Wacana, 2026)
The rapid growth of the online gaming industry, especially first-person shooter games like Valorant, has led to increased screen time among teenagers and young adults. Prolonged exposure to digital devices can cause eye health issues collectively known as Computer Vision Syndrome (CVS). Computer Vision Syndrome encompasses symptoms such as eye strain, blurred vision, headaches, and dry eyes. This study aims to determine the prevalence of Computer Vision Syndrome among Valorant players in the Indonesian Valorant Community and to identify contributing factors associated with Computer Vision Syndrome symptoms. A descriptive cross-sectional study was conducted with 102 respondents from the High Velocity (HIVE) Community, a part of the Indonesian Valorant Community. Data were collected via an online questionnaire and analyzed using univariate statistical methods. A total of 85.3% of participants reported experiencing Computer Vision Syndrome symptoms. Most respondents with Computer Vision Syndrome were male, with an average age of 21.63 years, and had a university-level education. Longer screen time, improper viewing distance, and refractive errors were significantly associated with the occurrence of Computer Vision Syndrome. Computer Vision Syndrome is a prevalent issue among Valorant players in Indonesia. Education on visual ergonomics, regulated screen time, and regular eye examinations are essential to reduce Computer Vision Syndrome risk.